Healthcare providers' knowledge and handling of impairments after intensive unit treatment: A questionnaire survey. Issue 4 (30th December 2019) - Jensen, Emilie K.; Poulsen, Lone M.; Mathiesen, Ole; Estrup, Stine
Abstract : Background: Numerous patients experience long‐term impairments after discharge from the intensive care unit (ICU), including physical, psychological and cognitive deficiencies. This study aims to investigate the knowledge and handling of post‐intensive care impairments among Danish doctors and nurses in the medical and surgical wards. Methods: An electronic questionnaire survey was distributed to consultants and development nurses, head nurses and assistant head nurses at departments of abdominal surgery and internal medicine of hospitals with an ICU in the Region Zealand of Denmark. Results: We invited 350 employees to participate, 48% responded. Most participants, 82.8% nurses and 86.6% doctors, reported their knowledge of in‐hospital needs of the ICU patients to be average or higher. Sixty per cent of doctors reported having average or higher knowledge of the patients' post‐discharge needs. More than half the doctors (60.2%) reported that they "Rarely" or "Never" addressed possible ICU‐related impairments in the discharge summary. During hospital admission, 22.9% replied "No screening performed" for physical impairment, while the rates for psychological and cognitive impairments were 70.7% and 57.3%, respectively. Most respondents believed that doctors (92.8%) and nurses (92.1%) in the ward and ICU doctors (89.4%) play an important role in detecting ICU‐related impairments; 63.8% felt that general practitioners play a key role. Conclusion: Doctors and nurses generally reported having average or higher knowledge of ICU patients' in‐hospital needs, but few screened systematically for ICU‐related impairments. Most respondents believed that detecting these problems is a shared responsibility between professionals in the primary and, especially, the secondary healthcare sector.